Detection of Internal Wave With Multi-Satellite Cross-Track Interferometric Synthetic Aperture Radar Imaging Technique - Tung-Cheng Wang; Jean-Fu Kiang (IEEE Access)
Internal waves, which can wreak havoc on underwater activities, are difficult to detect because their signatures on the sea surface are easily obscured by wind waves. In this work, a cross-track interferometric synthetic aperture radar (XTI-SAR) imaging technique based on multiple satellite-pairs is proposed to detect the surface signatures of internal wave, with higher height accuracy and finer horizontal resolution that can be achieved by using conventional satellite pair. By superposing the XTI-SAR images acquired from multiple satellite pairs, random features of wind waves are filtered out to reveal the surface signatures of internal wave, without compromising the horizontal resolution. Three internal-wave events are simulated to demonstrate the efficacy of the proposed approach, with height accuracy of centimeters and spatial resolution of 14 m, under wind speed of $U_{{1}0} ≤ 6$ m/s.